2017
DOI: 10.1093/gbe/evx216
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Functional Impact of Neanderthal Ancestry in Western Asia

Abstract: Neanderthals contributed genetic material to modern humans via multiple admixture events. Initial admixture events presumably occurred in Western Asia shortly after humans migrated out of Africa. Despite being a focal point of admixture, earlier studies indicate lower Neanderthal introgression rates in some Western Asian populations as compared with other Eurasian populations. To better understand the genome-wide and phenotypic impact of Neanderthal introgression in the region, we sequenced whole genomes of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 56 publications
(85 reference statements)
4
16
0
Order By: Relevance
“…Based on f 4 ratios, we find that proportions of introgression are relatively low and very similar among the Levantine and southern Arabian populations (Figure 2; Table S3). These findings are consistent with previous findings that Near Eastern populations have lower levels of introgression than other non-Africans (Lazaridis et al, 2016; Rodriguez-Flores et al, 2016; Taskent et al, 2017). The low levels of introgression in these populations cannot be attributed to gene flow from sub-Saharan Africa as some of these Levantine and southern Arabian populations (such as the Druze and Saudis) were found to have minimal sub-Saharan ancestry (Vyas et al 2017a).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on f 4 ratios, we find that proportions of introgression are relatively low and very similar among the Levantine and southern Arabian populations (Figure 2; Table S3). These findings are consistent with previous findings that Near Eastern populations have lower levels of introgression than other non-Africans (Lazaridis et al, 2016; Rodriguez-Flores et al, 2016; Taskent et al, 2017). The low levels of introgression in these populations cannot be attributed to gene flow from sub-Saharan Africa as some of these Levantine and southern Arabian populations (such as the Druze and Saudis) were found to have minimal sub-Saharan ancestry (Vyas et al 2017a).…”
Section: Discussionsupporting
confidence: 93%
“…The Levantine and southern Arabians have significantly more introgression than sub-Saharan Africans as depicted by significantly negative D statistics in Figure 4. Furthermore, the Levant and southern Arabia have significantly less introgression than most other non-Africans as depicted by the significantly positive D statistics in Figure 4; these findings are consistent with previous studies of Near Eastern populations (Lazaridis et al, 2016; Rodriguez-Flores et al, 2016; Taskent et al, 2017). The Levantine and southern Arabian pooled populations also share very similar D statistic values when compared to other non-African pooled populations (compare top and bottom of Figure 4; Table S6).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was highlighted by different studies that showed that the introgression of diverse genes related to immune functions, such as the OAS cluster, TLR1, or the histocompatibility complex from Denisovans and Neanderthals shaped the genetic landscape of present-day Eurasian, but not African, communities. Genomic sequences and expression data from lymphoblastoid cell lines from 421 individuals of European and African ancestry confirmed that the TLR1-TLR6-TLR10 genetic loci, presenting signs of local positive selection and repeated introgression from both Neanderthal and Denisovan genomes [24][25][26], showed a significantly higher expression in individuals carrying archaic-like alleles than in individuals carrying the nonintrogressed modern human alleles [2,26,27]. The expression of these genes has shaped human immune responses against different types of pathogens.…”
Section: Neanderthals and Denisovans Contributed To Shaping The Modermentioning
confidence: 81%
“…However, whatever the potential benefits of archaic introgression in the past, alleles of Neanderthal origin have been also associated with several neurological, dermatological, and immunological phenotypes, indicating an influence of ancient admixture on current disease risk in humans (Mozzi et al, 2017;Simonti et al, 2016;Taskent et al, 2017). For example, introgressed alleles associated to the immune system response can increase the risk of inflammation or autoimmunity under the environmental factors changing overtime (Barreiro & Quintana-Murci, 2010;Brinkworth & Barreiro, 2014;Corbett et al, 2018;Sironi & Clerici, 2010; S. C. Stearns, 2012).…”
Section: Genomic Signatures Of Adaptive Introgression From Archaic Tomentioning
confidence: 99%